The effect of l-arginine on catalase and arginase enzyme activity levels in sreptozotocin induced diabetic rats - Ozan, ST; Tasdemir, B (Blackwell Publishing, 2005)
[Abstract Not Available]
IUBMB 50th Anniversary Symposium -- JUL 02-07, 2005 -- Budapest, HUNGARY